The Effect of Level Paddy Bran Addition as Carbohyrate Source to Characteristic Market Vegetable Waste Silage - Supitri, Weni; Mustaring, Mustaring (AgriSains, 2020)
This study aims to determine the effect of the level of adding rice bran as a source of carbohydrates on the characteristics of market vegetable waste silage. Market vegetable waste used includes cabbage, chicory and corn husks. This study used a completely randomized design (CRD) consisting of 4 treatments and 5 replications with P0 = market vegetable waste without adding rice bran (0%), P5 = market vegetable waste added with 5% rice bran, P10 = market vegetable waste added with bran rice 10%, and P15 = market vegetable waste added by 15% rice bran. The variables observed were pH, temperature and total colonies of lactic acid bacteria, silage of market vegetable waste. Data were analyzed with Analysis of Variance and continued with Duncan's advanced test. The results of the ANOVA showed that the treatment had no significant effect (P> 0.05) on the pH, temperature and total colonies of lactic acid bacteria. The conclusion is that the addition of the level of rice bran as a source of carbohydrates does not have a significant effect on the characteristics of market waste silage.